1992
DOI: 10.1113/jphysiol.1992.sp019106
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP‐and beta‐agonist‐activated chloride conductance of a toad skin epithelium.

Abstract: SUMMARY1. The control by intracellular cyclic AMP and ,-adrenergic stimulation of chloride conductance was studied in toad skin epithelium mounted in a chamber on the stage of an upright microscope. Impalement of identified principal cells from the serosal side with single-barrelled conventional or double-barrelled Cl--sensitive microelectrodes was performed at x 500 magnification. For blocking the active sodium current 50 ftM-amiloride was present in the mucosal bath.2. When clamped at transepithelial potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…No effect is observed with agonists of α 2 -receptors. These effects are fundamentally different from those that are observed following β-adrenoceptor stimulation, which increases the baseline level of G Cl through elevation of cellular cAMP, and may result both from stimulation of glandular Cl -secretion [23] and activation of baseline current in the gland-free epithelium [27]. The mechanism of the voltage-activated G Cl appears to be more complex than the sole gating of an anion channel.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…No effect is observed with agonists of α 2 -receptors. These effects are fundamentally different from those that are observed following β-adrenoceptor stimulation, which increases the baseline level of G Cl through elevation of cellular cAMP, and may result both from stimulation of glandular Cl -secretion [23] and activation of baseline current in the gland-free epithelium [27]. The mechanism of the voltage-activated G Cl appears to be more complex than the sole gating of an anion channel.…”
Section: Discussionmentioning
confidence: 97%
“…A special property of the Cl -pathway is the development of a large transepithelial current, which is due to the activation of a conductive pathway in response to serosa-positive electrical potentials and is carried by the flow of Cl -from the mucosal to the serosal side [13]. Since G Cl can also be activated after inhibition of phosphodiesterase by theophylline [10], β-adrenergic agonists and membrane-permeable analogues of cAMP [27], it has been proposed that cAMP regulates the conductive Cl -pathway by virtue of a shift in the voltage sensitivity of the activation. However, a subsequent study has shown that cAMP alters the properties of the Cl -pathway far more fundamentally [9].…”
Section: Introductionmentioning
confidence: 98%
“…The view of control by cAMP was originally based on the observation that activation of G Cl could be enhanced by theophylline, an inhibitor of PDE, in frog skin [35] or restored in the toad skin in which conductance had been adaptationally reduced [24]. This was corroborated by the finding that application of the β-adrenergic agonist, isoproterenol, or membrane-permeable analogues of cAMP appear to shift the conductance/voltage relationship of apical Cl -channels towards lower voltages [89]. Subsequent studies [26] indicate that this effect, which looks like a shift, actually reflects a fundamental change of the kinetics and selectivity patterns of the anion pathway in response to high concentrations of cAMP.…”
Section: Signalling Pathwaysmentioning
confidence: 94%
“…Whilst earlier studies suggested that cAMP is a decisive messenger at the apical Cl -channels of MRC [39,89], it now appears that the role of cAMP is considerably more complex. The view of control by cAMP was originally based on the observation that activation of G Cl could be enhanced by theophylline, an inhibitor of PDE, in frog skin [35] or restored in the toad skin in which conductance had been adaptationally reduced [24].…”
Section: Signalling Pathwaysmentioning
confidence: 96%
See 1 more Smart Citation